PENGARUH KEDISIPLINAN DALAM PENDIDIKAN MILITER TNI AU TERHADAP TINGKAT STRESS - Ary Wicaksono, David (Widya Warta, 2017)
The research aims to learn the relationship betwen effects of disciplinary education of the air force Indonesian National Armed Force toward male students stress. The subject of thr research is male students of Semaba. Measurement tool that is used is the scale. The analysis of regression using SPSS 18 version program becomes the method of data analysis. According to the analysis, correlation p = 0,010 (p<0,05). It shows that there is effects of disciplinary educatian toward male studentr stress. From the analysis it can be concluded that the variable of disciplinary education can be used as the predictor to predict male students stress of Semaba.